O direito à água frente à mercantilização: um estudo do acesso à água pelas pessoas em situação de rua em Goiânia - Farias, Fernanda Sales França de (2024)
Although the theme of water concerns environmental issues, it is possible to see the relevance of economic discourse in this context. It appears that, on the one hand, we have the recognition of water as a human right, but, on the other, there was its commodification, from the moment it was declared as a good of economic value. So, the research intends to study how the conception of water as a commodity impacts its access by the homeless population, since, when assigning an economic value to a good, its access, consequently, will be determined by having economical means of obtaining it. For this, the bibliographical and documentary research technique was proposed as a methodology, as a means of studying the process of recognizing water as a human right and discussions about water as a commodity. In addition, the empirical research technique was used with an observational procedure method with interviews with homeless people in Centro, Campinas and Universitário neighborhoods in Goiânia, public servants from CentroPop and Serviço Especializado em Abordagem Social, as well as volunteers from non-governmental organizations (Invisível GO, Grupo de Regeneração Chico Xavier and Tio Cleobaldo). Finally, the research outlines a profile of access to water by the group studied, demonstrating that access is insufficient, given the few public water points in the city and is even more difficult when it comes to access to water for hygiene. Furthermore, the stigma suffered by this population stands out and also how inaccessibility to water is one of the various ways in which discourses that make these people invisible and dehumanize are materialized.